Pengembangan Modul IPA Berbasis Integrasi Islam Dan Sains Untuk Meningkatkan Hasil Belajar Siswa Kelas Vi Min 2 Mojokerto - Benny Angga Permadi (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2018)
The Development of IPA Module based on Islamic and scientific integration to Increase the Result Study of the Students in the sixth class in MIN 2 Mojokerto. This development of IPA module based on Islamic and scientific integration in MIN 2 Mojokerto is based on gaps include; first, the IPA result studies of the sixth class students in MIN 2 shows that 30% of students have not reach KKM score which is established 70; second, the IPA teaching material which is used has not an interesting design and the concept based on Islamic and scientific integration; third, there is not a teaching material which guides the students to get IPA concept as a medium for them to increase their beliefs toward Allah SWT. According to the research problem which is explained before, so the development of IPA module based on Islamic and scientific integration becomes an important thing to do. This development is to produce the development of IPA module based on Islamic and scientific integration; to know the specification, the use of, the effectiveness, and the interesting thing of IPA module based on Islamic and scientific integration in MIN 2 Mojokerto. The development of this module uses ADDIE (Analysis, Design, Development, Implementation, dan Evaluation) development, model. These subject assessments for feasibility module are material expert, design expert, linguist, learning expert, and also the sixth class students in MIN 2 Mojokerto. The principal ways of this research are initial conditions analysis, the development of a planning module, a writing module, and an assessment module. The collecting data which are used include questionnaires, interview, and the result of studies.